Synthesis and biological activity of benzo-fused 7-deazaadenosine analogues. 5- and 6-substituted 4-amino- or 4-alkylpyrimido[4,5-b]indole ribonucleosides - Tichý, Michal; Pohl, Radek; Tloušt'ová, Eva; Weber, Jan; Bahador, Gina; Lee, Yu-Jen; Hocek, Michal (Bioorganic & medicinal chemistry, 2013)
Two series of new 4-aminopyrimido[4,5-b]indole ribonucleosides bearing phenyl or hetaryl group at position 5 or 6 have been prepared by Suzuki or Stille cross-coupling reactions employing X-Phos ligand with (het)arylboronic acids or stannanes. A series of 4-substituted nucleosides has been also prepared by Pd-catalyzed cross-couplings or nucleophilic substitution. Some of these compounds displayed moderate antiviral activities against HCV and dengue viruses.
Keywords: Anti-dengue virus activity; Cell Survival; ribonukleosidy; Ribonucleosides; indoly; Adenosine; palladium; Humans; HeLa buňky; Catalysis; Indoles; Nucleosides; Palladium; Pyrimido[4,5-b]indoles; Dengue Virus; lidé; Suzuki and Stille cross-coupling; Hep G2 Cells; HL-60 Cells; buňky Hep G2; HeLa Cells; antivirové látky; HL-60 buňky; Antiviral Agents; nádorové buněčné linie; virus dengue; Cell Line, Tumor; Hepacivirus; katalýza; viabilita buněk; adenosin